Stories that deliver business insights - Cayla, Julien; Beers, Robin; Arnould, Eric J. (MIT, 2014)
Ethnography has often been portrayed as a "fly on the wall" technique, with anthropologists lurking in people's homes to observe consumers' unadulterated lives. The authors argue that this description does not do justice to the way ethnography actually works in the corporate world or to ethnography's increasingly important role in formulating business strategy. The authors' research across a variety of companies suggests that ethnography - artful in situ investigation into what customers do and feel and how they talk about what they do and feel - is a powerful tool to use to gain insights into your market. To arrive at a more in-depth understanding of how corporations use ethnography to their advantage, the authors conducted interviews with executives in various industries worldwide, including Ford and Wells Fargo. Where data analytics and surveys provide flattened snapshots, ethnography contributes an empathic understanding of how consumers live, work and play through gritty and detailed descriptions. Whether conveyed in video format, presentations or reports, these stories describe how people confront and surmount the hurdles they encounter in meeting their responsibilities and fulfilling their hopes in our globalized consumer culture. By delving into the richness of people's life stories, ethnographic research can pivot companies away from less meaningful segmentation parameters, such as demographics or purchase history, and toward those that drive behavior, such as purpose and intent. Quantitative techniques such as factor analysis can subsequently be applied to locate and size market segments. Consistent with the idea that ethnography helps organizations deal more effectively with market complexities, the executives the authors interviewed often talked about ethnography as having helped them sort out puzzling data. While these discussions call into dispute the perception that ethnography is merely an exploratory technique, they also underline the point that ethnographic stories often provide insight into consumer behavior that is hard to come by in other ways